Extractive removal of both basic and non-basic nitrogens from fuel oil by dicarboxyl-modified polyethylene glycol: Performance and mechanism. (15th October 2019) - Jiang, Xingmao; Zhu, Shuang; Gao, Jiajun; Yu, Yaqian; Xiong, Chunyan; Li, Chunxi; Yang, Weimin
Highlights: Replacing –OH of PEG with –OCH2 COOH can promote removal of basic nitrogens. dcPEG-600 is a green and effective extractant for both basic and non-basic nitrogens. High performance of dcPEG-600 is due to proper mole ratio between –COOH and C-O-C. Abstract: Polyethylene glycol [PEG, H(OCH2 CH2 )n OH] like PEG-600, a green extractant for organic N-compounds in fuel oil, was very active for non-basic nitrogens but not effective for basic ones. Modification of PEG that replaced –OH group with –OCH2 COOH group can produce HOOCCH2 (OCH2 CH2 )n OCH2 COOH (dcPEG). For denitrogenation, dcPEG-600 was highly effective for both basic and non-basic nitrogens. N-distribution coefficient [ D N, (μgN ·gdcPEG −1 )/(μgN ·goil −1 )] of dcPEG-600 to n -octane can reach as high as 200 for indole, 92.6 for pyrrole, 42.0 for quinoline, and 81.5 for pyridine, respectively. Besides, denitrogenation selectivity of dcPEG-600 to toluene ( D N / D toluene ) can amount to 462 for indole, 230 for pyrrole, 146 for quinoline, and 366 for pyridine, respectively. The high performance was ascribed to contribution of active O atom on ether group and active H atom on –COOH group. The active O atom (Lewis basic site) formed H-bond with the non-basic nitrogen (Brønsted acid). The active H atom (Brønsted acidic site) not only interacted with the basic one (Lewis base) but also brought in the good selectivity. Moreover, dcPEG-600 was still effective for real oil and could be recycled for several times without the denitrogenation performance significantly decreasing.